The significance of Al-Farabi’s spiritual and ethical heritage in personal moral consciousness formation: a philosophical-religious perspective (Eurasian Journal of Religious Studies, 2026)
The spiritual and ethical legacy of Abu Nasr Al-Farabi is examined in this article within the framework of current religious and philosophical discussions on moral growth. The aim of the study is to examine Al-Farabi's ideas of "the virtuous individual-the virtuous society-the virtuous State," emphasizing the connection between moral behavior, intellectual thought, and spiritual culture. It places special emphasis on the role that morality, education, and reason play in reaching human perfection. The study's foundation is a thorough philosophical-religious studies examination of Al-Farabi's principal works, such as "On Achieving Happiness" and "The Attitudes of the Inhabitants of the Virtuous City," together with comparative philosophical and ethical techniques. This research work shows that by combining spiritual values with logical knowledge, Al-Farabi's teachings offer a methodical framework for comprehending the development of moral consciousness. According to the findings of the work, applying the ideas into practice helps people grow into morally upright people and strengthens the moral and spiritual culture of modern society. The study is important from a scientific and practical point, providing a useful tool for tackling contemporary issues like moral decline and the crisis of values, with real-world implications in spiritual growth, ethical education, and the encouragement of moral behavior.Keywords: culture, philosophy, excellence, ethics, knowledge